An injection-nulling switch for switched-capacitor circuit applications - Chan, Pak Kwong (2009)
This paper presents a new switch, the injection-nulling switch (INS), for minimizing both the charge injection error and the clock feedthrough error in switched-capacitor circuits. Comprised of two identically designed MOS transistors and